Experimental Study on the Surface Integrity of Aircraft Gears in Spindle Barrel Finishing - Fu Zhengyu; Liu Qingsong; Deng Mingming; Shao Wen (Jixie chuandong)
An experimental study is conducted to investigate the surface integrity in spindle barrel finishing of 14CrMnSiNi2MoA aviation cylindrical spur gears. The surface morphology, residual stress, microhardness, microstructure of aviation gears before and after barrel finishing are systematically studied by professional instruments. The results indicate that the gear surface integrity can be significantly improved by spindle barrel finishing. The surface roughness of the gear reduces to less than 0.2 μm and the average residual compressive stress of the gear surface increases by about 45%. The hardness of the gear surface also increases. The results of surface roughness and residual stress distribution before and after barrel finishing reveal that the increase of residual compressive stress and decrease of roughness of the gear surface increase gradually from the root to the top of the gear, which provides a basis for the setting and designing of processing parameters in barrel finishing.